2006
DOI: 10.1002/bip.20641
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dimerization of Serratia marcescens endonuclease on water dynamics

Abstract: The dynamics and structure of Serratia marcescens endonuclease and its neighboring solvent are investigated by molecular dynamics (MD). Comparisons are made with structural and biochemical experiments. The dimer form is physiologic and functions more processively than the monomer. We previously found a channel formed by connected clusters of waters from the active site to the dimer interface. Here, we show that dimerization clearly changes correlations in the water structure and dynamics in the active site not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Both values are smaller than 0.96 evaluated from the bulk, and β res is lower in the monomer than that in the subunit B of the dimer. Such differences clearly demonstrate that water in this area in the subunit B of the dimer is less affected by both the protein and DNA, which is the same phenomenon observed in the protein systems [20]. …”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…Both values are smaller than 0.96 evaluated from the bulk, and β res is lower in the monomer than that in the subunit B of the dimer. Such differences clearly demonstrate that water in this area in the subunit B of the dimer is less affected by both the protein and DNA, which is the same phenomenon observed in the protein systems [20]. …”
Section: Resultsmentioning
confidence: 65%
“…The MD simulations of the free SMnase systems [20] reproduced the experimentally observed the metal coordination number and structural geometry of Mg-ligand cluster [14]. Theoretical studies of hydration properties of Mg 2+ [39,40] showed that in water it takes18.4 kcal/mol to remove one water molecule from a hexa-hydrated Mg 2+ .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations